The effects of consecutive night shifts and shift length on cognitive performance and sleepiness: a field study. Issue 2 (3rd April 2017) - Haidarimoghadam, Rashid; Kazemi, Reza; Motamedzadeh, Majid; Golmohamadi, Rostam; Soltanian, Alireza; Zoghipaydar, Mohamad Reza
Abstract : Introduction . The aim of this study was to evaluate the effects of consecutive night shifts (CNS) and shift length on cognitive performance and sleepiness. Materials and methods . This study evaluated the sleepiness and performance of 30 control room operators (CROs) working in 7 nights, 7 days, 7 days off (7N7D7O) and 30 CROs working in 4 nights, 7 days, 3 nights, 7 days off (4N7D3N7O) shift patterns in a petrochemical complex on the last night shift before swinging into the day shift. To assess cognitive performance, the n -back test, continuous performance test and simple reaction time test were employed. To assess sleepiness, the Karolinska sleepiness scale was used. Results . Both schedules indicated that the correct responses and response times of working memory were reduced ( p = 0.001), while intentional errors and sleepiness increased during the shift work ( p = 0.001). CNS had a significant impact on reaction time and commission errors ( p = 0.001). Conclusion . The main duty of CROs at a petrochemical plant is checking hazardous processes which require appropriate alertness and cognitive performance. As a result, planning for appropriate working hours and suitable number of CNS in a rotating shift system is a contribution to improving CRO performance and enhancing safety.